The Effect of Mathematical Disposition on Students' Mathematical Performance - ., Wahyudin; ., Marzuki; Suryadi, Didi; Cahya, Endang; Shofia Maulida, Aya (KnE Social Sciences, 2024)
Mathematical disposition is a tendency to think and act in a positive way. Changes in learning activities due to Covid-19 have an impact on the learning environment. This study aims to obtain an overview between dispositions and mathematical performance in online learning, and the effect of disposition on the mathematical performance of high school students. This research is concerned with correlation and regression analysis that relates mathematical dispositions to mathematical performance on relation and function material. The research was conducted on 70 high school students from the city of Bandung. To analyze data related to correlation and regression, Pearson product-moment was used. The results of this study were as follows: 1) A significant positive correlation was observed between mathematical disposition scores (X), and mathematical performance scores (Y) with a correlation coefficient of r = 0.42, this means that r2 = 17.2%. The variation in students’ mathematical performance (Y) can be explained by the student’s mathematical disposition variable (X). 2) Based on the regression equation Y = 34.211 + 0.548X, this shows that because the X coefficient is 0.548 > 0 (positive) and significant, the mathematical disposition variable has a positive effect on mathematical performance in online learning. Keywords: high school students, mathematical disposition, mathematical performance